Pemanfaatan Kahoot! Sebagai Media Belajar Untuk Meningkatkan Minat Siswa Dalam Menambah Vocabulary di SMK Bina Profesi Pekanbaru - Amalina Amalina; Esti Raihana; Warminah Warminah (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2024)
Learning media is one aspect of increasing the success of learning. Using creative and interesting learning media will certainly make it easier for students to accept lessons. Kahoot! is a learning media in the form of a game that can be accessed on the website. The purpose of this outreach is to see whether the learning media Kahoot! useful for increasing students' interest in adding vocabulary. The methods used in carrying out this socialization are lecture methods, application use demos and question and answer sessions. The series of socialization activities include: (1) Students do practice questions regarding vocabulary manually (without game teaching media) (2) Then go to the step of providing an explanation about the Kahoot! learning application! (3) During this explanation session students will be explained the steps for using the Kahoot! application, (4) Followed by a question and answer session, (5) After the question and answer session several students are selected to come forward to try the Kahoot! (6) Students download the Kahoot! on their smartphone/laptop and work on the questions given. (7) Students do practice questions regarding vocabulary in the Kahoot! application. This socialization was carried out at the Pekanbaru Professional Development Vocational School. The subjects of this socialization are students of class X Tourism Travel Business with a learning time of 2 hours.